Ventricular empyema presenting as a complication of pneumococcal meningitis in a toddler - Parthasarathi Muthusamy; Madhumitha Chellappan Subramaniam; Ayyammal Palaniappan; Ponnusamy Shanmugam; Balasenthilkumaran Meda Rabindranath; Balavinoth Ramakrishnan; Ramakrishnan Tirupur Chinnappan Ramalingam (Wolters Kluwer Medknow Publications, 2023)
Streptococcus pneumoniae is a major pathogen in the pediatric population causing life-threatening infections ranging from pneumonia and meningitis to sepsis, and it is now a vaccine-preventable infection. Recently, pneumococcus is emerging as a cause of multidrug-resistant infection, resistant to ≥3 classes of antibiotics. Here, we discuss a case of ventricular empyema in a toddler due to S. pneumoniae. He was not vaccinated against pneumococcus. He had ventriculitis, ventricular empyema, and obstructive hydrocephalus. He was managed with external ventricular drainage of pus, followed by a ventriculoperitoneal shunt, and received 6 weeks of intravenous antibiotics, followed by oral antibiotics. He recovered with residual neurological sequelae and showed an improvement on follow-up visits.